Phase in optics - Perinova, Vlasta (World Scientific, 1998)
Includes bibliographical references (p. 415-441) and index.; This book is devoted to the classical and quantum phases in wave and particle optics from the viewpoint of both theory and applications. Wave and beam light optics are reviewed in considerable detail, featuring optical imaging and holography in linear optics and phase conjugation methods in nonlinear optics. Photon optics is embodied here as quantum optics with the modes treated as quantum harmonic oscillators. The importance of the Wigner function for the phase space description in the context of canonical quantization is respected and the method of quasidistributions related to operator orderings in the second-quantized theory is exposed. The history of the quantum phase problem, characterized by renewed interest in the solution to the problem, is included and brought up to date. Approaches based on exponential phase operators, discrete phase states, the enlargement of the Hilbert space of the harmonic oscillator leading to the phase representations and distributions, together with solutions motivated by the quasidistributions, are introduced. The operational approach to the quantum phase is contrasted with the previous formalisms. The results of the study of the coherent states and the ordinary squeezed states from the viewpoint of the quantum phase and those of the analysis of the quantum statistics of phase-related special states of the light field are provided. The quantum phase is also treated with respect to quantum interferometry, particle